Georeferenced Point Clouds: A Survey of Features and Point Cloud Management - Otepka, Johannes; Ghuffar, Sajid; Waldhauser, Christoph; Hochreiter, Ronald; Pfeifer, Norbert (ISPRS international journal of geo-information, 2013)
This paper presents a survey of georeferenced point clouds. Concentration is, on the one hand, put on features, which originate in the measurement process themselves, and features derived by processing the point cloud. On the other hand, approaches for the processing of georeferenced point clouds are reviewed. This includes the data structures, but also spatial processing concepts. We suggest a categorization of features into levels that reflect the amount of processing. Point clouds are found across many disciplines, which is reflected in the versatility of the literature suggesting specific features.